KORELASI MEDIA SOSIAL TIKTOK DALAM PEMBENTUKAN KARAKTER PADA MAHASISWA PGSD - Erwin Putera Permana (PENDIDIKAN SAINS DAN TEKNOLOGI, 2023)
A popular social media platform is TikTok. Total downloads of the Tiktok app in 2022 were 500 million times. Indonesia became the country with the most downloads at 11%. It is undeniable that social media has become a habit and is likely to be able to shape the character of its users. Quantitative research to obtain data from survey questionnaire results with experimental methods. The research subjects were 218 PGSD Level 2 UNP Kediri students with a sampling of 25% of the 55 respondents. The results found that 96.4% of respondents access TikTok every day, 96.5% of TikTok content triggers stress, 78.2% students lost concentration, 69.1% of students lost control of themselves, and 43.6% were anxious if they didn't access TikTok every day. Judging from the findings based on the intensity of time, stress, concentration, self-control and anxiety that arise, TikTok social media affects changes in student character. TikTok social media seems to be an addiction if someone is not able to control themselves and can be a learning tool if used properly. For example, inspiration in constructing music and dance, education, business, self-image, news and also honing public speaking skills.